Theoretical and experimental investigation of hydration behavior of choline salicylate ionic liquid in the presence of L- glycine - Negin Ammari; Hemayat Shekaari; Behrang Golmohammadi; Fariba Ghaffari; Mohammed Taghi Zafarani-Moattar (Scientific Reports)
Abstract Choline salicylate [Ch][Sal] an active pharmaceutical ingredient ionic liquid (API-IL) aqueous solutions in the presence of L-glycine that is a simple simulated biological media has been studied. The thermodynamic and transport properties including density, speed of sound, viscosity and electrical conductance have been studied under atmospheric pressure and a temperature range of (288.15 to 318.15) K. The key thermophysical properties, including apparent molar volume (V φ ), apparent molar isentropic compressibility (κ φ ), viscosity B-coefficient, ion association constant (K a ), and limiting molar conductivity (Λ 0 ) were derived from these data. The transfer properties (Δ tr V φ 0 , Δ tr κ φ 0 , and ΔB tr ) demonstrate the dominance hydrophilic-hydrophilic interactions between the IL and L-glycine in the studied systems that increased with L-glycine concentration. The COSMO results revealed that differences in molecular size, stability, and hydration behavior of [Ch][Sal] and L-glycine, with [Ch][Sal] exhibiting stronger hydration due to its larger size and hydrogen bonding capacity. These findings provide insights into solute-solvent interactions and potential synergistic effects of [Ch][Sal] and L-glycine as a simple simulated biological media contributing to the optimization of pharmaceutical formulations and related activities.